A qualitative examination of the content validity of the EQ-5D-5L in patients with type 2 diabetes. Issue 1 (December 2015) - Matza, Louis; Boye, Kristina; Stewart, Katie; Curtis, Bradley; Reaney, Matthew; Landrian, Amanda
Abstract Background The EQ-5D is frequently used to derive utilities for patients with type 2 diabetes (T2D). Despite widely available quantitative psychometric data on the EQ-5D, little is known about content validity in this population. Thus, the purpose of this qualitative study was to examine content validity of the EQ-5D in patients with T2D. Methods Patients with T2D in the UK completed concept elicitation interviews, followed by administration of the EQ-5D-5L and cognitive interviewing focused on the instrument's relevance, clarity, and comprehensiveness. Results A total of 25 participants completed interviews (52.0 % male; mean age = 53.5 years). Approximately half (52 %) reported that the EQ-5D-5L was relevant to their experience with T2D. When asked if each individual item was relevant to their experience with T2D, responses varied widely (24.0 % said the self-care item was relevant; 68.0 % said the anxiety/depression item was relevant). Participants frequently said items were not relevant to themselves, but could be relevant to patients with more severe diabetes. Most participants (92.0 %) reported that T2D and/or its treatment/monitoring requirements had an impact on their quality of life that was not captured by the EQ-5D-5L. Common missing concepts included food awareness/restriction (n  = 13, 52.0 %); activities (n  = 11, 44.0 %); emotional functioning other than depression/anxiety (n  = 8, 32.0 %); and social/relationship functioning (n  = 8, 32.0 %). Conclusions The results highlight strengths and potential limitations of the EQ-5D-5L, including missing content that could be important for some patients with T2D. Suggestions for addressing limitations are provided.